Diagnosis of hepatic steatosis by contrast-enhanced abdominal computed tomography - Monjardim,Rodrigo da Fonseca (2013)
Objective To evaluate the diagnostic capacity of abdominal computed tomography in the assessment of hepatic steatosis using the portal phase with a simplified calculation method as compared with the non-contrast-enhanced phase. Materials and Methods In the present study, 150 patients were retrospectively evaluated by means of non-contrast-enhanced and contrast-enhanced computed tomography. One hundred patients had hepatic steatosis and 50 were control subjects. For the diagnosis of hepatic steatosis in the portal phase, the authors considered a result of < 104 HU calculated by the formula [L - 0.3 × (0.75 × P + 0.25 × A)] / 0.7, where L, P and A represent the attenuation of the liver, of the main portal vein and abdominal aorta, respectively. Sensitivity, specificity, positive and negative predictive values were calculated, using non-contrast-enhanced computed tomography as the reference standard. Results The simplified calculation method with portal phase for the diagnosis of hepatic steatosis showed 100% sensitivity, 36% specificity, negative predictive value of 100% and positive predictive value of 75.8%. The rate of false positive results was 64%. False negative results were not observed. Conclusion The portal phase presents an excellent sensitivity in the diagnosis of hepatic steatosis, as compared with the non-contrast-enhanced phase of abdominal computed tomography. However, the method has low specificity.